Covid-19 Pandemic: Mental Dynamics of Quarantine and Social Isolation - Jainish Patel; Prittesh Patel (Journal of Behavior Therapy And Mental Health, 2020)
This paper explores the two major preventive concepts of the unpredictable life-threatening viral infection caused by Coronavirus that is ravaging the entire world from the beginning of the year 2020, as it pertains to mental health. Through scientific consultations, the expectation is that effective vaccine for the Coronavirus disease-2019 (COVID-19) may not come into the market this year. Two (among others) preventive measures, namely Social Distancing and Quarantine are suggested by the World Health Organization (WHO). Using the principle of explorative research, this study established the flipside of quarantine and social distancing from the metal health perspective. It was discovered that there is a relationship between a long period of self-isolation and a high probability of concerned persons having anxiety, stress, and depression, which gradually leads to mental and emotional health issues. Consequently, mental health affects the overall health and affects how we handle different situations during the Covid-19 pandemic. By considering this important matter, this article recommended different ways to improve mental health during the pandemic in the quest to keep oneself away from psychological issues arising due to the Covid-19 situation.
Keywords: Coronavirus